WORD FORMATION IS AN INTEGRAL PART OF KNOWLEDGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the word formation as an element of knowledge in cognitive linguistics, as well as problems the formation of complex words.